Recurrent Perianal Abscess in a Patient With Hermansky-Pudlak Syndrome Associated Granulomatous Colitis: A Case Report - UPRAK, TEVFİK KIVILCIM (My University, 2021)
Hermansky-Pudlak syndrome (HPS) is a rare genetic disease consisting of the triad of oculocutaneous albinism, bleeding diathesis, and pigmented reticuloendothelial cells. In HPS patients' granulomatous colitis could be an additional feature and perianal abscess could be seen in such patients. We report a patient with HPS-associated granulomatous colitis, refractory to medical treatment, and perianal involvement. Patients with HPS-associated granulomatous colitis and perianal involvement may require multiple surgical interventions and there is no consensus yet for treatment in such patients.
Keywords: Colitis; General surgery; Hermansky-Pudlak syndrome; Proctitis